Coping Stres Pasangan Remaja Menikah Dini di Nagari Tanjung Beringin Kecamatan Lubuk Sikaping Kabupaten Pasaman - Nidia Fertisia S; Fadhilla Yusri; Budi Santosa; Hidayani Syam (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
The background of this research is that there were four couples of early married teenagers aged around 17-19 years who married early due to promiscuity which led to pregnancies outside of marriage. to his wife and children so they look like they are experiencing stress. The focus of this research is to find out the Coping of Stress for young couples who marry early in Nagari Tanjung Beringin, Lubuk Attitudeing District, Pasaman Regency. This research method uses descriptive qualitative research that is telling or describing something with what is happening in the field. The key informants of this study were four couples of early married teenagers and the supporting informants in this study were families and neighbors of early married couples. Data collection methods in this study are observation, interview and documentation methods. Data analysis techniques, namely data reduction, data presentation, and drawing conclusions or verification, and data validity techniques, namely data triangulation. The results of the study concluded that the form of coping stress for young married couples is emotional focuse coping which is carried out by observing early married couples where not all couples can solve problems when these problems occur. Judging from the four coping pairs displayed by early married teenage couples, Emotion focuse coping is how to avoid problems by getting angry, arguing which causes the husband to leave the house and bring silence so that the situation is calmer and the wife cries shutting herself up at home to calm herself from her anger after anger subsided then the couple tried to solve the problem.